PENGARUH DAN MANFAAT BAGI HASIL TERHADAP JUMLAH SIMPANAN DEPOSITO MUDHARABAH BANK SYARIAH MANDIRI DI INDONESIA - MUHAMMAD FATIBUT TIMAMI (Universitas Negeri Surabaya, 2013)
Profit sharing is one of the factors that determine customer to store/deposit it in the bank. Although not all customers in the save/deposit it is based on the profit motive. In the fourth quarter of 2011 and third quarter of 2012 decreased for a given outcome independent Islamic banks to depositors, but the amount of fixed deposits mudaraba increased. This study aims to determine whether there are implications and benefit for the deposits to total deposits mudaraba. The data used are secondary and primary data. The secondary data derived from published reports of Mandiri Islamic Bank. Based on the results of t-test showed that the results are significantly affected variable total of mudaraba deposits in Mandiri Islamic Banks. Primary data obtained from interviews from the samples which choose with random (random sampling) concluded that the results provide good benefits as a client, a Muslim, as well as benefits for social life, which in turn also provide benefits for the total of mudaraba deposits. Keywords: Islamic Bank, Profit sharing, Deposits